Evaluasi Efisiensi dan Efektivitas Program Bantuan Sosial dalam Mengurangi Kemiskinan di Negara Berkembang - Afandi, Ahmad; Zein, Ahmad Wahyudi; Rinaldi, Riyan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Social assistance programs are key public policy tools used by developing countries to reduce poverty and improve societal welfare. However, the implementation of these programs often encounters challenges such as targeting inaccuracies, weak inter-agency coordination, limited budgets, and institutional capacity constraints. This article aims to evaluate the extent to which social assistance programs have succeeded in reducing poverty, focusing on two primary dimensions: efficiency (resource allocation and operational costs) and effectiveness (tangible outcomes for beneficiaries). The study adopts a qualitative approach, utilizing literature review and secondary data analysis from national and international institutional reports. The findings indicate that the success of these programs largely depends on the delivery mechanisms, transparency, and integrated monitoring systems. Policy recommendations include improving the accuracy of beneficiary data, strengthening digital systems, and implementing evidence-based periodic evaluations to enhance program performance in the future.